Prevalence of irritable bowel syndrome and its association to mental health among the private university students of Dhaka, Bangladesh. - A B M Nahid Hasan; Md Asaduzzaman; Most Nourin Mahfuj; Rashedul Islam; Md Mohasin Kabir Bhuyan; Prosenjit Basak; Azaz Bin Sharif (PLOS Global Public Health)
Irritable Bowel Syndrome is a common gastrointestinal disorder linked to psychological distress and lifestyle factors. In Bangladesh, young adults may experience exacerbated IBS symptoms due to particular hardships. This study aims to evaluate the prevalence of IBS and its association with mental health status among private university students. A cross-sectional study conducted between November 2023 and May 2024 and involved 550 students aged 19-40 years from three private universities in Dhaka, Bangladesh selected through convenience sampling. Data were collected via in-person interviews using a semi-structured questionnaire that included the Rome III and the DASS-21 scale. Pearson's χ² test was used to explore associations and multiple logistic regression was employed to identify factors influencing IBS. The prevalence of IBS among the students was 31.63%. Female students had higher odds of developing IBS compared to males (AOR = 1.71, 95% CI: 1.19 to 3.36). Psychological distress was strongly associated with IBS, with students experiencing severe anxiety (AOR = 3.14, 95% CI: 1.11 to 7.24) and stress (AOR = 3.39, 95% CI: 1.16 to 6.79) showing increased odds of IBS. Additionally, satisfaction with academic major (AOR = 0.46, 95% CI: 0.18 to 0.96) indicates 54% lower odds of IBS compared to those who were unsatisfied. Physical activity (AOR = 0.64, 95% CI: 0.29 to 0.90) shows a 36% reduction in the odss of IBS with moderate physical activity (20-60 minutes per day). Daily vegetable consumption (AOR = 0.81, 95% CI: 0.67 to 0.89) suggested a 19% lower odds of IBS. Malnutrition (AOR = 1.77, 95% CI: 1.11 to 2.82) was associated with a 77% increased odds of IBS. The findings emphasize the importance of implementing comprehensive campuswide health promotion programs that address psychological distress, promote healthy lifestyle choices, and provide nutritional guidance to alleviate the burden of IBS among them.